The equation of the line passing through the points (x1 , y1) and (x2 , y2) is given by ( y - y1) = [( y2 - y1)/ ( x2 - x1)] * ( x - x1)

We have to find the line passing through ( 2 , 3) and ( 4, 6). Substituting the values given we get:

y - 3 = [( 6 - 3) / (4 - 2)] * ( x - 2)

=> y - 3 = (3/2)* ( x - 2)

=> y - 3 = (3/2)x - 3

=>** y = (3/2)x; slope 3/2, intercept 0.**

Given the points ( 2,3) and (4, 6) passes through a line.

We know that the equation of the line is given by :

y-y1= m(x-x1) where (x1,y1) is any point on the line and m is the slope.

Let us determine the slope.

==> m = (6-3)/(4-2) = 3/2

==> y -3 = (3/2) ( x-2)

==> y-3 = (3/2)x - 3

**==> y= (3/2)x **